Therapeutic Communication of Kiai and Mental Cadres as Media for Mental Health Resilience for People with Mental Disorders During the Covid-19 Pandemic - Wahyuningsih, Sri (Universitas Islam Negeri Raden Intan Lampung, 2022)
The increasing number of People with Mental Disorders during the Covid-19 pandemic was due to a lot of pressure from outside and inside, including genetic, environmental, and psychological factors. What makes people most depressed during a pandemic is environmental factors because the economy is declining, and losing their jobs causes people to be stressed and ultimately depressed. This research aims to discover, analyze, and explore the Therapeutic Communication of Kiai and Mental Cadre as a Media for Mental Health Resilience for People with Mental Disorders during the Covid-19 Pandemic Period. This research method is descriptive qualitative with a single instrumental case study approach. The research subjects are Kiai and mental cadres. The object of the research is the therapeutic communication of Kiai and mental cadres as a medium for mental health resilience for People with Mental Disorders during the Covid-19 pandemic. Using purposive sampling, the informants were selected according to the research objectives. Data collection techniques use interviews, observation, documentation, audio-visual materials, and literature review. The data analysis technique uses data reduction, data display, and concluding. The data validity technique uses source triangulation, method triangulation, and member checks. The research location is in Bangkalan, the Bani Amrini mental institution. The research results are that in the resilience of People with Mental Disorders during this pandemic, Kiai and mental cadres use therapeutic communication, including communication-based on Islamic religious therapy, therapeutic communication based on work activities, daily communication-based therapeutic communication, and hydro- or water-based therapeutic communication. The theory used in analyzing the results of this research is George Herbert Mead's Symbolic Interaction Theory with the concepts of Mind, self, and society.